2014
DOI: 10.1093/nar/gku1065
|View full text |Cite
|
Sign up to set email alerts
|

Chk2 and REGγ-dependent DBC1 regulation in DNA damage induced apoptosis

Abstract: Human DBC1 (Deleted in Breast Cancer 1; KIAA1967; CCAR2) is a protein implicated in the regulation of apoptosis, transcription and histone modifications. Upon DNA damage, DBC1 is phosphorylated by ATM/ATR on Thr454 and this modification increases its inhibitory interaction with SIRT1, leading to p53 acetylation and p53-dependent apoptosis. Here, we report that the inhibition of SIRT1 by DBC1 in the DNA damage response (DDR) also depends on Chk2, the transducer kinase that is activated by ATM upon DNA lesions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…4 Quantification of protein levels were normalized to loading control and for phosphorylated proteins to total proteins. Proteins were transferred to a PVDF membrane (Protran, Merck Millipore, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Quantification of protein levels were normalized to loading control and for phosphorylated proteins to total proteins. Proteins were transferred to a PVDF membrane (Protran, Merck Millipore, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…2 We previously demonstrated that CCAR2, phosphorylated by ATM/ATR and cooperating with the checkpoint kinase Chk2 and the proteasome subunit REG γ , negatively regulates the NAD + -dependent histone deacetylase SIRT1, promoting p53 activation and apoptosis induction in presence of DNA damage. 3, 4 Recently, we also reported that CCAR2 itself modulates the activity of Chk2 towards KRAB-associated protein 1 (KAP1), thus influencing the repair of DNA breaks. 5 …”
mentioning
confidence: 99%
“…Subsequent studies revealed that SIRT1 inhibition by DBC1 results in increased acetylation of p53 that, in turn, mediates p53-dependent apoptosis following DNA damage [16, 17]. Inhibition of SIRT1 by DBC1in the DNA damage response (DDR) depends on ATM-dependent Chk2 activation [18]. This Chk2 activation in turn promotes phosphorylation of the 11S proteasome activator REGγ, which increases REGγ–DBC1 interaction and SIRT1 inhibition [18].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of SIRT1 by DBC1in the DNA damage response (DDR) depends on ATM-dependent Chk2 activation [18]. This Chk2 activation in turn promotes phosphorylation of the 11S proteasome activator REGγ, which increases REGγ–DBC1 interaction and SIRT1 inhibition [18]. Caspase-dependent processing of DBC1 has also been implicated in its pro-apoptotic activity during tumor necrosis factor alpha (TNFα)-mediated apoptosis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a low-penetrance breast cancer gene, CHEK2 , is also located in proximity to the detected signal. This gene encodes a cell-cycle checkpoint kinase that cooperates with p53, BRCA1 and ATM and regulates cell division in response to DNA damage 153 . Germline mutations and variants of CHEK2 had been implicated in susceptibility to several cancer types 154–158 , including familial pancreatic cancer 41,42,159 .…”
Section: Common Low-risk Susceptibility Locimentioning
confidence: 99%